Anomalous electrocaloric behaviors in (anti)ferroelectrics: a mini-review - Li, Feng; Wang, Chunchang; Shan, Lei (Frontiers in Chemistry, 2024)
Solid-state cooling, represented by electrocaloric effect (ECE) in (anti)ferroelectric materials, emerges as an alternative green refrigeration technology by virtue of its high efficiency and miniaturization and is expected to substitute for conventional vapor-compression method. A significant progress has been made in developing high-performance EC materials since its revival. However, anomalous EC behaviors are frequently observed, including asymmetrical and negative EC profiles, and the physical mechanism behind is still under debate. Its rationalization is of great importance since full utilization of anomalous EC behaviors could enhance EC strength and/or cooling capacity. This mini-review gives a brief of research advances for EC anomaly in (anti)ferroelectrics, with the hope of providing some thoughts in design of reconstructed refrigeration cycles and superior EC materials for applications in solid-state cooling devices.